2015
DOI: 10.1016/j.ijnurstu.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous home-care nursing staff are more engaged in their work and less likely to consider leaving the healthcare sector: A questionnaire survey

Abstract: In developing strategies for retaining nursing staff in home care, employers and policy makers should target their efforts at enhancing nursing staff's autonomy, thereby improving their work engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 33 publications
(43 reference statements)
2
35
0
1
Order By: Relevance
“…Professional intra-and inter-relationships and teamwork in palliative care were often based on shared trust and nurses working in home-care perceived the value of teamwork more than nurses working in hospices (Maurits, de Veer, van der Hoek, & Franck, 2015;Moir, Roberts, Martz, Perry, & Tivis, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional intra-and inter-relationships and teamwork in palliative care were often based on shared trust and nurses working in home-care perceived the value of teamwork more than nurses working in hospices (Maurits, de Veer, van der Hoek, & Franck, 2015;Moir, Roberts, Martz, Perry, & Tivis, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, nurses’ engagement and organisational commitment are pivotal to attentive caring for end‐of‐life patients (Freeney & Tiernan, ). Nurses in palliative care valued their work as integral of a team approach and essential to managing and resolving the complexities of a demanding clinical field (Maurits et al, ). Amidst the changing Italian nursing environment, palliative care offered nurses the opportunity for expand their scope of practice.…”
Section: Relevance To Clinical Practice: Nurses’ Work Engagement To Hmentioning
confidence: 99%
“…Nursing Staff Panel participants are recruited via a random sample of Dutch healthcare employees provided by the Dutch Employee Insurance Agency. This procedure helps generate a representative group with respect to age, sex, region and employer (Maurits et al., ). In 2014, there was a supplementary recruitment drive in which participants working in home care were asked to invite up to four colleagues to join the Nursing Staff Panel.…”
Section: Methodsmentioning
confidence: 99%
“…However, to date the research on factors that attract nurses to home care has tended to focus on general work characteristics. For instance, previous studies have shown that autonomy is important (Ellenbecker, Boylan, & Samia, ; Maurits, De Veer, & Francke, ; Tummers, Groeneveld, & Lankhaar, ). Little is known about the attractiveness of people‐centred and integrated home care.…”
Section: Introductionmentioning
confidence: 99%
“…Disabled and older people tend not to want institutional care, but rather to receive care in a friendly environment such as their own homes . The need for home care is rising in many Western European countries due to ageing population and to governmental policies aiming at replacing institutional care with home care . In most OECD countries, between half and three‐quarters of all formal long‐term care is provided in home care settings …”
Section: Introductionmentioning
confidence: 99%